New record of Prozostrodon brasiliensis (Eucynodontia: Prozostrodontia) from its type-locality (Upper Triassic, Southern Brazil): comments on the endocranial morphology - Kerber, Leonardo (2020)
Here we described a new specimen (UFRGS-PV-0543-T) of the non-mamaliaform cynodont Prozostrodon brasiliensis, collected in the Faixa Nova locality (Santa Maria City, State of Rio Grande do Sul, Brazil), which is referred to the Upper Triassic, Hyperodapedon Assemblage Zone. The new specimen includes a portion of the cranium (fragmented nasals, lacrimals, prefrontals, frontals, palatines, vomer, and fragments of the right premaxilla, left maxilla, and pterygoid), preserving the natural endocast of the nasal cavity, and a fragmented right dentary. The specimen is assigned to P. brasiliensis based on the absence of the postorbital bar, the shape and extension of the snout, the height of the horizontal ramus of the dentary, the position of the Meckelian groove, the morphology of the last postcanine (the only one with the crown partially preserved), and fitting size. The natural endocast is composed of sediment that filled in the nasal cavity. On the dorsal surface of the endocast, there is a longitudinal median sulcus formed by the median bony ridge. Laterally to this median sulcus, there is a longitudinal sulcus on each side formed by the lateral crests. The vomer is low and robust, tapering anteriorly and showing a dorsal groove along its entire length. Other aspects of the endocranial anatomy of UFRGS-PV-0543-T, including wide olfactory region and marked oval-shaped olfactory bulbs, are similar to those of other Late Triassic probainognathian cynodonts.